2015
DOI: 10.1007/s00221-015-4390-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of the reticulospinal system in recovery of skilled reaching after cortical stroke: initial results from a model of ischemic cortical injury

Abstract: The purposes of this pilot study were to create a model of focal cortical ischemia in Macaca fascicularis and to explore contributions of the reticulospinal system in recovery of reaching. Endothelin-1 was used to create a focal lesion in the shoulder/elbow representation of left primary motor cortex (M1) of two adult female macaques. Repetitive microstimulation was used to map upper limb motor outputs from right and left cortical motor areas and from the pontomedullary reticular formation (PMRF). In subject 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 70 publications
0
51
0
1
Order By: Relevance
“…First, HRP may bleed into un-intended spinal segments after injection resulting in false positive findings. Additionally, the use of WGA-HRP, a trans-synaptic tracer, does not eliminate the possibility that the origin of ipsilateral labeling is subcortical nuclei rather than an iCST or that ipsilateral projections are “re-crossed” branching collaterals of initially crossed fibers [2, 9]. Another major concern in animal studies is that the separation of sensory and cortical motor components is difficult to establish [32].…”
Section: Icst In Non-primatesmentioning
confidence: 99%
See 3 more Smart Citations
“…First, HRP may bleed into un-intended spinal segments after injection resulting in false positive findings. Additionally, the use of WGA-HRP, a trans-synaptic tracer, does not eliminate the possibility that the origin of ipsilateral labeling is subcortical nuclei rather than an iCST or that ipsilateral projections are “re-crossed” branching collaterals of initially crossed fibers [2, 9]. Another major concern in animal studies is that the separation of sensory and cortical motor components is difficult to establish [32].…”
Section: Icst In Non-primatesmentioning
confidence: 99%
“…Supporting these findings, unilateral lesions proximal to the CST decussation failed to induce deficit at the ipsilateral limb, and iCST fibers failed to rescue limb function after contralateral pyramidal lesions [49]. Simultaneously, electrical stimulation of affected hemisphere after stroke in rodent model demonstrated improved recovery of skilled functions through promoting axonal sprouting at the subcortical (red nucleus) and spinal levels [9, 50]. However, controversial findings still suggest a role of iCST in recovery from injury.…”
Section: Evidence Of Reorganization Of Cst After Injury In Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, reticulospinal (RS) hyperexcitability resulted from loss of balanced inhibitory, and excitatory descending RS projections after stroke is the most plausible mechanism for poststroke spasticity (19). On the other hand, animal studies have strongly supported the possible role of RS pathways in motor recovery (2036), while recent studies with stroke survivors have demonstrated that RS pathways may not always be beneficial (37, 38). The relation between spasticity and motor recovery and the role of plastic changes after stroke in this relation, particularly RS hyperexcitability, remain poorly understood among clinicians and researchers.…”
Section: Introductionmentioning
confidence: 99%